The effects of connectedness on health-promoting and health-compromising behaviors in adolescents: evidence from a statewide survey - Yang, Fang; Tan, Kit Aun; Cheng, Wendy J. Y. (Springer, 2014)
Using a social ecological perspective, we examined the effects of connectedness in multiple domains on health-promoting and health-compromising behaviors among Asian American (AA), Pacific Islander (PI), and Caucasian/White American (WA) adolescents in California. After adjusting for age, gender, and socioeconomic status, the following consistent results emerged across the three ethnic groups: (a) community connectedness increased the odds of physical activity; (b) internal, family, and school connectedness decreased, whereas friend connectedness increased, the odds of substance use; and (c) internal and family connectedness decreased the odds of violent behavior. We also found specific ethnic variations pertaining to the effects of connectedness. Friend connectedness increased the odds of violent behavior for AAs and WAs, but not for PIs. Meanwhile, community connectedness increased the odds of substance use and violent behavior for AAs and PIs, but decreased the odds of these behaviors for WAs. Findings for healthy dietary behavior were inconsistent across ethnic groups and connectedness domains. Our overall findings suggest that the effects of connectedness were more salient for health-compromising behaviors than for health-promoting behaviors. Health prevention and intervention efforts in adolescents could target the role of their connectedness to their multiple social domains.